Assesment of the use of zero-emission vehicles and microbial fertilizers in beverage production. (1st November 2017) - Özilgen, Mustafa
Abstract: Greenhouse gas emissions of food production increased from 680 to 2.2 Gt/year between 1961 and 2011. Greenhouse gases are not emitted as a consequence of the field level agriculture or farm level husbandry only, the later stages of production such as processing, packaging and transportation make additional contributions to both energy utilization and the subsequent greenhouse gas emissions. Huge energy savings reported in the literature for individual production steps of food production usually correspond to a modest percentage in the total farm-to-fork production chain. Chemical fertilizers are usually the most energy intense inputs of these chains. Energy utilization and the subsequent CO2 emissions are calculated based on the data adapted from the literature for the entire farm-to glass-production chain of ten beverages. The calculations are then repeated for the cases where chemical fertilizers are replaced with their microbial counterparts and the vehichles and the agricultural equipment are replaced with their zero-emission counterparts. These replacements are estimated to reduce energy utilization from 18, 393 to 3508 MJ/t and the emission from 493 to 43 kg CO2 /t in powdered coffee drink production. If the same replacements are implemented globally and the same average reductions, e.g., 38.1% as calculated in this study are achieved, 0.84 Gt/year of greenhouse gas emission may be prevented globally. Highlights: Carbon dioxide emissions as a consequence of energy use are calculated. Energy savings are assessed for alternative processes and microbial fertilizers. Huge energy savings in a production step may make modest contribution to total. Replacing chemical fertilizers with microbial ones may lead to major savings. Highest reductions in CO2 emission occurred in instant coffee production.